Azithromycin Attenuates Bleomycin-Induced Pulmonary Fibrosis Partly by Inhibiting the Expression of LOX and LOXL-2 - Tong, Xiang; Zhang, Shijie; Wang, Dongguang; Zhang, Li; Huang, Jizheng; Zhang, Tianli; Fan, Hong (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis (PF) is a chronic and progressive process of tissue repair. Azithromycin (AZM) may be beneficial for the treatment of PF because AZM has anti-inflammatory and immune regulatory roles and inhibits remodeling, but the mechanism is not entirely clear. In this study, we established a mouse PF model induced by bleomycin (BLM) and primary mouse lung fibroblasts stimulated by transforming growth factor (TGF)-β1 to explore the possible mechanisms of AZM in PF. Results showed that AZM reduces mortality and lung inflammation and attenuates BLM-induced PF in mice. AZM effectively reduced the expression of α-smooth muscle actin (SMA) and type I collagen. Meanwhile, expression of lysyl oxidase (LOX) and lysyl oxidase-like protein (LOXL)-2 in the lung tissue of mice after AZM treatment was significantly lower than in the BLM group. In addition, this study found that AZM significantly inhibits the TGF-β1/Smad and JNK/c-Jun signaling pathways in vivo, and expression of a-SMA, type I collagen, LOX and LOXL-2 in the lung tissue of mice treated with AZM was significantly lower than that in the BLM group. In vitro, AZM also effectively inhibited type I collagen, LOX, LOXL-2 and JNK-c-Jun signaling pathways in TGF-β1-stimulated primary mouse fibroblasts, and this effect was similar to that of a JNK-specific inhibitor (SP600125). In conclusion, AZM effectively attenuated BLM-induced PF in mice, which may play a role by partially inhibiting the JNK/c-Jun and TGF-β1/Smad signaling pathways and reducing production of LOX and LOXL2.